Integration of Digital Branding and Library Services in Enhancing Generation Z Engagement - Naufalia Rahmadhani; Dwi Putri Aulia (Codex: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This study aims to analyze how the integration of digital branding strategies and digital library services enhances Generation Z’s engagement and reading interest. The research is motivated by the shifting information behavior in the digital era, where Generation Z relies heavily on technology and social media as primary sources of information access. Employing a qualitative descriptive approach, the study involved librarians and active students who regularly use digital library services. Data were collected through in-depth interviews, participant observation, and digital documentation, and analyzed using Miles and Huberman’s interactive model. The results indicate that the success of integrating digital branding with digital services lies in the consistency of visual identity, interactive communication by librarians, and the ease of technological access that together shape a positive user experience. These three elements synergistically enhance user satisfaction and loyalty while strengthening the library’s image as an adaptive and relevant institution in the era of digital transformation. The study contributes to the theoretical enrichment of library digital branding practices and offers practical recommendations for libraries to design user experience–driven communication and service strategies.